Characteristics of Cancer Survivors Living in Poverty in the United States: Results From the 2020 Behavioral Risk Factor Surveillance System Survey. Issue 11 (6th November 2022) - Coughlin, Steven S.; Datta, Biplab; Williams, Lovoria B.; Bevel, Malcolm; Cortes, Jorge E.
Abstract : PURPOSE: There has been increasing concern over the high cost of oncology care and its long-lasting impact on the well-being of cancer survivors. METHODS: We examined characteristics of impoverished cancer survivors in the United States, including their physical and mental health, using data from the 2020 Behavioral Risk Factor Surveillance System. We used binomial logistic regressions for binary outcome variables, and negative binomial regressions for count variables, to estimate the odds ratios (ORs) and incident rate ratios (IRRs) of the physical, mental, and socioeconomic-related health factors for low-income cancer survivors versus higher-income survivors. We compared the ORs and IRRs for low-income cancer survivors with those of higher income cancer survivors. RESULTS: There was a two-fold increased odds (adjusted OR, 2.33; 95% CI, 1.86 to 2.91) of having fair/poor health for low-income cancer survivors compared with higher-income cancer survivors. There was an almost two-fold increased odds (adjusted OR, 1.97; 95% CI, 1.50 to 2.59) of not being able to see a doctor among low-income cancer survivors, and a 42% lower odds (adjusted OR, 0.58; 95% CI, 0.39 to 0.86) of having health insurance coverage for low-income cancer survivors compared with higher-income survivors. Incidence rate ratios for physical (IRR, 1.52; 95% CI, 1.31 to 1.75) and mental (IRR, 1.53; 95% CI, 1.26 to 1.86) unhealthy days were significantly higher among low-income cancer survivors compared with nonpoor cancer survivors. CONCLUSION: Strategies are available to ameliorate financial hardship at multiple levels. Implementation of these strategies is urgently needed.